LEARNING ENGLISH AS A FOREIGN LANGUAGE AND THE NEW MILLENNIALS’ LITERACIES. - Ana Osuna, Carlos Zavala, Ma. Reynoso and Ileana Osuna (International Journal of Research Science and Management, 2018)
Although Mexico has made efforts to teach English to students for more than seven decades, the results of its policies have not been as expected. However, young people who have reached successful levels of language proficiency could show us other factors they interact with that let them achieve those proficiency levels. These students, called millennials, learn differently from their predecessors and their learning scenarios are no longer found only at school. Internet, an environment where they invest half of their day, could be more than a mere distractor as has been stated. This work is part of an unfinished research that seeks to analyze the relationship between the use of the Internet for leisure purposes and the learning of English as a foreign language in young students. A mixed perspective with a sequential explanatory design is used, where at first the data of a survey applied to students reveals that those with language proficiency use their interaction with different leisure activities on the Internet to learn and improve their linguistic competence. This daily contact becomes a fund of knowledge that allows them to develop their level of English, both in informality and in formal language learning at school.